2020
DOI: 10.3389/fpsyg.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Attentional Selection Following Gaze and Arrow Cues

Abstract: Although most studies on social attention have shown undistinguishable attentional effects in response to eye-gaze and arrow cues, recent research has found that whereas the orienting of attention triggered by eye-gaze is directed to the specific position, or part of the object looked at, arrows unselectively elicit attention toward parts of the environment. However, it is unclear whether this dissociation between gaze and arrow cues is related to social cognitive mechanisms such as mental state attribution (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Results suggest that when several placeholders are grouped into a perceptual object as a function of Gestalt principles of proximity (Experiment 2), gaze and arrows cues elicit attentional effects similar to those first reported by Marotta and colleagues ( [18], see [38] for replication). In particular, they showed that when objects were present in the display, eye-gaze cues directed attention to the specific part of the cued object, while arrow cues spread attention to…”
Section: Discussionsupporting
confidence: 78%
“…Results suggest that when several placeholders are grouped into a perceptual object as a function of Gestalt principles of proximity (Experiment 2), gaze and arrows cues elicit attentional effects similar to those first reported by Marotta and colleagues ( [18], see [38] for replication). In particular, they showed that when objects were present in the display, eye-gaze cues directed attention to the specific part of the cued object, while arrow cues spread attention to…”
Section: Discussionsupporting
confidence: 78%
“…However, a different pattern of results emerges in paradigms aiming at investigating qualitative differences between gaze and arrows. For example, whereas gaze direction orients attention to the specific spatial location or part of the object looked at, arrows spread attention through the whole cued object (Chacón-Candia et al, 2020 ; Marotta et al, 2012 ). Gaze seems to selectively focus attention on and automatically select the specific location/part of the object looked at, rather than simply initiating the orienting of attention, as arrows do (Marotta et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, gaze might trigger additional attentional processes, which might only be uncovered by approaches aimed at investigating qualitative differences between the two types of cue. For example, it has been found that whereas arrows spread their attentional facilitation through an entire cued object, gaze selectively orients the attention to the specific location or part of the object looked at (Marotta et al, 2012;Chacón-Candia et al, 2020). Beyond cueing paradigms, other tasks have shown distinctive properties of eye cues.…”
mentioning
confidence: 99%